Adaptation and the evolution of parasite virulence in a connected world - Wild, G; Gardner, A; West, SA (Nature Publishing Group, 2009)
Adaptation is conventionally regarded as occurring at the level of the individual organism, where it functions to maximize the individual’s inclusive fitness1,2,3. However, it has recently been argued that empirical studies on the evolution of parasite virulence in spatial populations show otherwise4,5,6,7. In particular, it has been claimed that the evolution of lower virulence in response to limited parasite dispersal8,9 provides proof of Wynne-Edwards’s10 idea of adaptation at the group level. Although previous theoretical work has shown that limited dispersal can favour lower virulence, it has not clarified why, with five different suggestions having been given6,8,11,12,13,14,15. Here we show that the effect of dispersal on parasite virulence can be understood entirely within the framework of inclusive fitness theory. Limited parasite dispersal favours lower parasite growth rates and, hence, reduced virulence because it (1) decreases the direct benefit of producing offspring (dispersers are worth more than non-dispersers, because they can go to patches with no or fewer parasites), and (2) increases the competition for hosts experienced by both the focal individual (‘self-shading’) and their relatives (‘kin shading’). This demonstrates that reduced virulence can be understood as an individual-level adaptation by the parasite to maximize its inclusive fitness, and clarifies the links with virulence theory more generally16.